The true cost of food - Laborde Debucquet, David; Parent, Marie; Piñeiro, Valeria (T20, 2020)
Modern food systems, though fundamental to human life, generate heavy costs to the environment and public health. These costs transcend borders and generations; therefore, they require international governmental action. We call on the G20 to lead action on this problem by (1) issuing a mandate to international organizations to develop a harmonized approach to measure the social cost of food, (2) coordinating international reform of current harmful policies, especially subsidies linked to the emission of greenhouse gasses or a nutritionally imbalanced food supply, that contribute to costs, and (3) setting an agenda to repurpose government resources previously used on harmful policies for reducing the costs remaining after reform of current policies through beneficial policies, such as agricultural R&D for sustainability, payment for ecosystem services, and food safety initiatives.